2022
DOI: 10.4085/1062-6050-0658.21
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Risk Factors for Noncontact Musculoskeletal Injury in Collegiate Swimmers: A Prospective Cohort Study

Abstract: Context: Shoulder pain is pervasive in swimmers of all ages. Yet due to a limited number of prospective studies, risk factors for injury in swimmers remain uncertain. Objective: To determine the extent to which the risk factors of previous injury, poor movement competency, erroneous freestyle swimming technique, and low perceived susceptibility to sport injury were associated with non-contact musculoskeletal injury in college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There is limited evidence from only a single study of youth swimmers demonstrating greater shoulder pain with swimming if they did not have a neutral position of the scapula with the Kibler Test. 35 In conflict with this finding is limited evidence from one study using Kibler Test 44 and one using visual inspection 41 which both describe no relationship between scapular position/dyskinesia and shoulder pain for youth swimmers. Moderate evidence for no relationship between scapular position and shoulder pain was determined from two studies across age groups, 10,36 one including youth and adolescent/adult swimmers employed digital inclinometry for assessing the scapula at various intervals of elevation 36 and the other 10 used visual inspection for swimmers across all age levels (age 8-77).…”
Section: Scapular Position/dyskinesiamentioning
confidence: 99%
See 4 more Smart Citations
“…There is limited evidence from only a single study of youth swimmers demonstrating greater shoulder pain with swimming if they did not have a neutral position of the scapula with the Kibler Test. 35 In conflict with this finding is limited evidence from one study using Kibler Test 44 and one using visual inspection 41 which both describe no relationship between scapular position/dyskinesia and shoulder pain for youth swimmers. Moderate evidence for no relationship between scapular position and shoulder pain was determined from two studies across age groups, 10,36 one including youth and adolescent/adult swimmers employed digital inclinometry for assessing the scapula at various intervals of elevation 36 and the other 10 used visual inspection for swimmers across all age levels (age 8-77).…”
Section: Scapular Position/dyskinesiamentioning
confidence: 99%
“…Five studies utilized various methods for analyzing core stability and endurance as a risk factor for developing shoulder pain. 11, 26,32,33,41,42 the timed side bridge, timed prone plank, timed ball bridge, and isokinetic peak torque testing for trunk flexion/extension. One study reported on youth swimmers, three were on adolescent/adult swimmers, and one included various age groups There is moderate evidence from two studies in youth swimmers that decreased trunk endurance is associated with the development of shoulder pain.…”
Section: Core Stability/endurancementioning
confidence: 99%
See 3 more Smart Citations